2020
DOI: 10.1001/jamanetworkopen.2019.21363
|View full text |Cite
|
Sign up to set email alerts
|

Clinician Identification of Birth Asphyxia Using Intrapartum Cardiotocography Among Neonates With and Without Encephalopathy in New Zealand

Abstract: IMPORTANCE Despite improvements in antenatal care and increasing cesarean delivery rates, birth asphyxia leading to neonatal encephalopathy (NE) continues to contribute to neonatal death and long-term neurodevelopmental disability. Cardiotocography (CTG) has been used in labor for several decades to detect a stressed fetus so that delivery can be expedited and NE avoided. OBJECTIVE To investigate whether experienced clinicians can detect and respond to abnormal readings from CTGs during the penultimate hour be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…We identified seven studies following full text screening, of which one had its data collected during a previous community-based cluster randomised controlled trial. These seven studies included neonatal encephalopathy as an outcome, of which 6 were case controls and 1 was a cluster randomised trial [ 11 – 17 ] (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified seven studies following full text screening, of which one had its data collected during a previous community-based cluster randomised controlled trial. These seven studies included neonatal encephalopathy as an outcome, of which 6 were case controls and 1 was a cluster randomised trial [ 11 – 17 ] (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Mullany et al [ 16 ] considered infants to have intrapartum-related moderate-severe neonatal encephalopathy provided they experienced intrapartum-related neonatal respiratory depression resulting in death of seizures and 2 of the following: lethargy, poor suck or respiratory rate less than 40 breaths per minute, observed anytime during the first 7 days of life. Lastly, Farquhar [ 11 ] et al describe the study to include only moderate and severe encephalopathic babies according to New Zealand’s Neonatal Encephalopathy Working Group of the Perinatal and Maternal Mortality Review Committee (PMMRC). The Committee defines neonatal encephalopathy as a clinically defined syndrome of disturbed neurological function within the first week of life in term infants (i.e., 37 weeks or older), manifested by difficulty initiating and maintaining respiration, depression of tone and reflexes, subnormal level of consciousness, and often, seizures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinicians assess the risk of acidosis and HIE by visually monitoring the EFM for characteristic FHR patterns such as the baseline, accelerations, and decelerations ( American College of Obstetricians and Gynecologists, 2014 ; Lear et al, 2018 ). Nevertheless, visual assessment of FHR tracings has low specificity and sensitivity as well as high intra- and inter-observer variability ( Farquhar et al, 2020 ). The application of computerized analysis to quantify FHR signals has been proposed to reduce intra- and inter-observer variability ( Keith and Greene, 1994 ).…”
Section: Introductionmentioning
confidence: 99%
“…There appear to be limitations for each of these steps.Farquhar and colleagues 8 designed a case-control study to examine whether abnormal readings can be identified on the continuous fetal heart rate monitoring strip, also known as a cardiotocograph (CTG). 8 The cases were all of neonatal encephalopathy in which there was at least 1 hour of CTG available in the penultimate hour before delivery. The authors excluded cases that included an acute peripartum event immediately prior to delivery as well as cases with a likely source of the neonatal encephalopathy that preceded the labor and delivery.…”
mentioning
confidence: 99%